Towards a Synodal Church - Czerny, Michael (Razón y fe, 2021)
Synodality expresses a fundamental characteristic of the Church’s identity: its essential communal dimension, its essential evangelising mission, under the guidance of the Holy Spirit. Pope Francis has opened this collaborative form of deliberation to vigorous participation by the entire People of God, which disposes the synodal orientation to a prayerful listening to the cry of the poor and the cry of the earth. Pope Francis himself models this synodal way.